"I Know It Is Going to Ruin Their Life:" Fortune-Telling, Agency, and Harm Reduction in Narratives Concerning Injection Initiation Assistance. (8th September 2021) - Weicker, Noelle P.; Whaley, Sara; Urquhart, Glenna; Park, Ju Nyeong; Sherman, Susan G.; Owczarzak, Jill
Abstract: Background: Considering most people who inject drugs (PWID) received help with the first injection, understanding the perspective of potential 'initiators' is a priority to inform harm reduction interventions. This paper examines how PWID narrate their experiences with injection initiation and assistance from the lens of their lived experience and perceptions of harm reduction. Methods: In-depth interviews were conducted with individuals who reported injection drug use and recent (past 30 days) opioid use in Baltimore ( N = 19) and Anne Arundel County ( N = 4), Maryland and analyzed using a narrative approach. Results: Respondents cast initiation events as meaningful transitions to a life characterized by predictable harms, including homelessness, infections, and social stigma. Respondents used examples from their personal experience to explain experiences with initiation and assistance by strategically attributing personal agency and predicting specific injection-related harms for initiates. In their narratives, respondents balanced notions of individual agency with harm reduction intentions by distinguishing between two forms of harm: perceived inevitable distal harm caused by long-term injection (e.g. socioeconomic decline) and potentially avoidable proximal harm caused by risky injection practices (e.g. overdose, HIV). Conclusions: These findings highlight opportunities for interventions targeting injection initiation events and support the implementation of safer injection training in interventions. This identity of the 'responsible drug user' could be leveraged to support employing peers to help mitigate harm among inexperienced PWID either through peer outreach or formal venues, such as overdose prevention sites.